2010
DOI: 10.1016/j.vetmic.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic potential of Chlamydophila

Abstract: 1The purpose of this article is to present the diseases induced in humans and animals by the 2 different species of Chlamydophila, after providing an overview on the history of these 3 infectious agents and their taxonomy. The route of transmission and the available methods for 4 prevention and control in the different animal species are reviewed. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
78
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 92 publications
0
78
0
3
Order By: Relevance
“…However, other studies have shown that one species may be isolated from various hosts (4,6,9,13,16,17). Host specificity may be viewed in terms of primary or principal hosts and occasional hosts (20), where the infection usually spreads from the primary host to occasional hosts living in close proximity. This is illustrated in Cp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, other studies have shown that one species may be isolated from various hosts (4,6,9,13,16,17). Host specificity may be viewed in terms of primary or principal hosts and occasional hosts (20), where the infection usually spreads from the primary host to occasional hosts living in close proximity. This is illustrated in Cp.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Condon and Oakey (6), we applied a Chlamydiaceae-specific primer pair to screen for positive samples that can be subjected to species identification. Although the immediate treatment of infections by all Chlamydophila species is based on administration of the same group of antibiotics (20), the zoonotic potential of the different species is not equal, and a species determination is therefore required for adequate disease control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic infection leads to characteristic diffuse granulomatous or pyogranulomatous inflammation of serosal surfaces. In contrast, C. abortus is primarily adapted to sheep and goats, where it can induce abortion, fetal death, and genital disorders (41). The agent also infects cattle, swine, and horses and rarely infects birds, but clinical manifestations are less frequent than in small ruminants.…”
mentioning
confidence: 99%